Searching for Traces of Ecological Nodes in the Formation of Resilient Coastal Areas: Gulf of Saros - Tachir, Gildis; Alali, Ahmed (Journal of Urban Culture Research, 2025)
Building the resilience of a dynamic environment is a difficult task, but coastal areas shaped by natural formations have existing resilience points. This article attempts to find traces of elements that identify points of resilience. The method applied in this effort is the mapping method. In line with this method, it is aimed to investigate the traces of ecology nodes by overlapping the map information of the place with different elements with axonometric graphical expression. The Gulf of Saros, which is on the eastern coast of the Aegean Sea, was selected as the sample area of the study. The geographical environmental values of the Gulf of Saros were examined. As a limitation, the traces of the ecological node points of the Erikli district, which are areas with different environmental values in the Gulf of Saros, were researched, and other settlements were not evaluated within the scope of the study. In this direction, the protection, development and environmental sustainability of the traces of ecological nodes will increase the resilience of the coastal city against disasters that may occur.